Basil's Knowledge of Astronomy - Yam, Colten Cheuk-Yin (Zeitschrift für antikes Christentum, 2022)
This paper explores Basil’s knowledge of astronomy. It shows that Basil must have learnt astronomy already from his youth. It also demonstrates why and how Basil holds a complex attitude towards astronomy (as shown in Homily in hexaemeron 1 and 6). Finally, by comparing Basil's knowledge of this science with the astronomical handbook of his time, it argues that Basil has made use of Origen but not lavishly copied him, and the level of his astronomical knowledge did not go beyond Cleomedes' Caelestia , which is the most elementary astronomical handbook in ancient times.